Simultaneous absorptiometric determination of copper, nickel, iron and cobalt in refinery process streams : potential on-line application. - Archery, Evelyn (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MSc (Chemistry and Polymer Science))--University of Stellenbosch, 2005.